Hidradenitis suppurativa of the nape: Description of an atypical phenotype related to severe early‐onset disease in men. Issue 2 (18th December 2018) - Agut‐Busquet, Eugènia; Romaní, Jorge; Ribera, Miquel; Luelmo, Jesús
Abstract: Some patients with hidradenitis suppurativa (HS) develop severe inflammatory lesions of the nape. Through a single‐center, cross‐sectional study with a total of 377 patients, we sought to compare patients with and without nape involvement, to determine whether disease severity is greater in these patients and to describe their clinical characteristics. Thirty patients (90% male) were identified as having nape involvement. Patients with versus without nape involvement had greater disease severity, earlier disease onset, a family history of HS, lower body mass, and higher Dermatological Life Quality Index and pain scores. Amongst them, involvement of the trunk and gluteal regions predominated. A significant univariate relationship existed between patients with nape involvement and male sex, early disease onset, family history, scalp and gluteal involvement, Canoui‐Poitrine phenotypes II and III, and Dowling–Degos disease. A significant multivariate relationship existed with early disease onset, Dowling–Degos disease, and phenotypes II and III.